A parameter study for co-processing of petroleum vacuum residue and oil palm empty fruit bunch fiber using supercritical tetralin and decalin. (1st October 2016) - Kim, Doo-Wook; Koriakin, Anton; Lee, Chang-Ha
Highlights: Co-processing of heavy oil and biomass was conducted using supercritical solvents. Positive effects on co-processing led to a high conversion of both feed materials. Residue conversion reached 86.4 wt% with only 0.8 wt% of coke formation. Fe3 O4 catalyst with H2 contributed to a significant suppression of coke formation. Abstract: Co-processing of petroleum vacuum residue (VR) and oil palm empty fruit bunch (EFB) fiber was carried out through the use of supercritical solvents. The effects of solvent (tetralin and decalin), temperature (400 and 450 °C), a catalyst, and hydrogen on the co-processing were evaluated according to residue conversion and product distribution analysis. The results were compared with only the VR upgrading results as well as the co-processing of VR and microcrystalline cellulose. Supercritical tetralin exhibited high reaction performance in both VR upgrading and co-processing of VR/EFB without significant coke formation, compared with the results in decalin. In the presence of H2, the Fe3 O4 catalyst contributed toward suppressing coke formation. The co-processing of VR/EFB using tetralin could achieve a residue conversion of 86.4 wt% with only 0.8 wt% of coke formation, showing more favorable conversion than that of VR/microcrystalline cellulose. Therefore, it led to a positive effect which improved the residue conversions and yielded a great quantity of light product.